Minecraft. The lost journals - Lafferty, Mur (Del Rey, 2019)
Max loves adventure and is always on the lookout for a new quest, while Alison enjoys following the rules, but when the two friends find the old, beat-up journal of someone called the Enchanter and they learn about the otherworldly realm called the Nether. The friends use the journals instructions to make the portal, then an accident forces them inside, needing a way to escape.